Modelling the growth, yield, and future climate suitability of underutilized tropical tuber crops-‘aroids’: A review (Current Horticulture, 2024)
Elephantfoot yam and taro are important aroids of tropical tuber crops and considered as underutilized in the context of  climate change and food security. This study focuses on the existing modelling studies on growth, yield, and future climate  suitability of elephantfoot yam and taro. Among different crop models, SUBSTOR-Aroids, AquaCrop, and WOFOST are tested  internationally to simulate the crop growth and yield of aroids. The QUEFTS model is tested in India for aroids in estimating  crop yield based on site-specific nutrient management. EcoCrop is used to predict the future climate suitability of aroids. This  review indicates very limited studies are available for aroids compared to other tropical tuber crops. This shows the necessity to  focus more on these underutilized aroids as they are superior in per hectare production to that of major foodgrain crops. This  review also recommends modelling studies on aroids to identify or develop a better model structure irrespective of the agro climatic conditions.
Keywords: Elephantfoot yam; taro; aroids; climate change; food security; crop models; climate suitability